2009
DOI: 10.1007/s10067-009-1185-0
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab dramatically ameliorated life-threatening diarrhea due to secondary amyloidosis associated with rheumatoid arthritis

Abstract: Severe diarrhea improved dramatically with administration of the humanized anti-interleukin-6 receptor antibody tocilizumab (TCZ) in a patient with secondary reactive amyloidosis, which was associated with rheumatoid arthritis (RA). A 53-year-old woman with RA went into hypovolemic shock because of severe watery diarrhea associated with gastrointestinal amyloidosis. The high-dose prednisolone therapy and glucocorticoid pulse therapy did not improve her intractable diarrhea. After TCZ administration, the life-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 15 publications
0
36
0
3
Order By: Relevance
“…Three case studies of reactive AA amyloidosis, complicated by RA reported the ameliorative clinical effect of tocilizumab on gastrointestinal symptoms due to intestinal amyloidosis [49][50][51]. Surprisingly, amyloid A fibril deposits were found to have disappeared in two cases after three injections of tocilizumab.…”
Section: Development Of Tocilizumab a Humanized Anti-il-6 Receptor Amentioning
confidence: 99%
See 1 more Smart Citation
“…Three case studies of reactive AA amyloidosis, complicated by RA reported the ameliorative clinical effect of tocilizumab on gastrointestinal symptoms due to intestinal amyloidosis [49][50][51]. Surprisingly, amyloid A fibril deposits were found to have disappeared in two cases after three injections of tocilizumab.…”
Section: Development Of Tocilizumab a Humanized Anti-il-6 Receptor Amentioning
confidence: 99%
“…RA (in more than 90 countries worldwide) [36][37][38][39][40][41][42] Castleman's disease (in Japan) [52,53] Systemic and polyarticular JIA (in Japan) [57][58][59] Candidate diseases for tocilizumab therapy: Systemic autoimmune diseases SLE [130] Systemic sclerosis [115] Giant cell arteritis and Takayasu arteritis [90,91] Polymyositis Organ specific autoimmune diseases Crohn's disease [73] Relapsing polychondritis [108] Multiple sclerosis, neuromyelitis optica Acquired hemophilia A [149] Chronic inflammatory diseases Adult-onset Still's disease [61][62][63][64][65][66][67][68] Reactive AA amyloidosis [48][49][50][51] Polymyalgia rheumatica [80,91] RS3PE [85] Spondyloarthritides [100,[102][103][104][105] Behcet's disease Uveitis GVHD [150] Autoinflammatory diseases (TRAPS) [152] Tocilizumab has been approved as a biological drug for the treatment of RA, Castleman's disease and juvenile idiopathic arthritis, and is expected to be applicable to various other autoimmune and inflammatory diseases. Abbreviations: RA, rheumatoid arthritis; JIA, juvenile idiopathic arthritis; SLE, systemic lupus erythematosus; RS3PE, remitting seronegative, symmetrical synovitis with pitti...…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Surprisingly, three months after the tocilizumab treatment amyloid A protein deposits had completely disappeared. Subsequently, two other cases of AA amyloidosis associated with RA also showed the ameliorative clinical effect of tocilizumab on gastrointestinal symptoms due to intestinal amyloidosis (Sato et al, 2009;Inoue et al, 2010) and in one of the two cases amyloid A fibril deposits were found to have disappeared after three courses of tocilizumab treatment. Moreover, Kishida et al reported observing the clinical ameliorative effect of tocilizumab on a patient with adult-onset Still's disease complicated by AA amyloidosis as well as marked regression of amyloid A protein in duodenal mucosa and submucosa after tocilizumab treatment (Kishida et al, 2010).…”
Section: The Clinical Effect Of Tocilizumab and Other Biologics On Aamentioning
confidence: 99%
“…TCZ treatment almost completely normalizes the serum SAA level because IL-6 signal is essential for the expression of SAA (Hagihara et al, 2005). Therefore, TCZ is very useful for the treatment of secondary amyloidosis (Sato et al, 2009;Inoue et al, 2010). …”
Section: Amyloidosismentioning
confidence: 99%